Protohistoric graveyards in Adam (Oman). Preliminary report on the 2013 and 2014 seasons of the French Archaeological Mission to Adam - Gernez, Guillaume; Giraud, Jessica (Proceedings of the Seminar for Arabian Studies, 2015)
The two latest campaigns of excavations at Adam (Oman) have yielded new data on the funerary architecture and practices in central Oman, and their evolution during protohistoric times. The investigations focused on two graveyards that have been in use during a long period that includes the Early Bronze Age, the Middle Bronze Age, and the Iron Age. A large variety of types are now attested, including the first Umm an-Nar tomb excavated in the area of Adam and forty Wadi Suq graves. In addition to the presentation of the main types of graves, we will try to reconstruct the history of both graveyards.